Revisiting National Identity: Contemporary Shifts in Pakistan’s Socio-Political Narrative - Jawad Hussain; Waheed Murad (Journal of Religion and Society, 2025)
This article examines the ongoing evolution and contestation of national identity in Pakistan, tracing its historical foundations in the Two-Nation Theory and subsequent transformations through Islamization, securitization, and elite-driven narrative construction. It analyzes persistent tensions between a centralized Islamic framework and the realities of ethnic, linguistic, and cultural diversity, exacerbated by key crises such as the 1971 secession, Zia-era reforms, and post-9/11 security paradigms. Focusing on contemporary shifts from 2018 to 2025, the study explores how political polarization, social media proliferation, globalization, economic crises, and demographic pressures have accelerated the fragmentation of traditional identity constructs while fostering hybrid and inclusive counter-narratives. Through qualitative discourse analysis and interpretive case studies, it highlights the socio-political implications of deepened institutional distrust, risks to cohesion, and emerging calls for pluralistic reimagining’s. Ultimately, the article argues that Pakistan stands at a pivotal moment where embracing diversity through secular-inclusive or federated models offers the most viable pathway toward renewed national resilience and democratic stability. Keywords: National Identity, Pakistan, Two-Nation Theory, Islamization, Ethnic Diversity, Political Polarization